DEVELOPING TOURISM IN CON DAO ISLAND, VIETNAM: ISSUES OF CONCERN - Quyen, Le Thi to (International Journal of Psychosocial Rehabilitation, 2020)
This research is to analyze potentials and drawbacks for tourism development at Con Dao island and determine factors attracted tourists to this island through site observation and Five Likert scale surveyed questionnaires. Questionnaires were conducted with a total of of 140 tourists used in statistical analyses. It is revealed that Con Dao is an area with rich and diverse tourism potentials, not only natural resources, but also humanities tourism resources to attract tourists. However, electricity and water issues, and environmental impacts are main concerns for tourism development in Con Dao island. To attract tourists to this destination, local governments and tourist agencies should focus on five elements namely: Tourist resources, material and technical facilities, infrastructure and human resources; Cuisine and human resources; Service prices; Security and safety; and Promotion. Some solutions related to environmental sanitation; infrastructure and technical facilities; human resources; tourism promotion; entertainment shopping activities are proposing to further improve the effectiveness of tourism activities on this island.